Through a Glass Darkly: Ideology, Education, Institution - Bannerji, Himani (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2024)
Equity, diversity, and inclusion (EDI)—or sometimes styled EDID by including decolonization—is an institutionalized response to demands for access, inclusion, recognition, and redistribution by communities of people excluded from traditional centres of power. Under the banner of EDI(D), educational institutions have launched an extensive program of adult education, seeking to “train” institutional actors to adhere to policies and root out bias in practice. In this paper, Bannerji situates the relations of EDI work within the broader framing of multiculturalism, racism, and ideologies of education in Canada. Drawing from Dorothy Smith’s unique articulations of ontology and ideology, Bannerji confronts the ideological praxis of EDI work and asks us to consider the politics of identity and pedagogy that constitute this particular conjuncture.